ANALISIS KEPUASAN KONSUMEN TERHADAP KONSUMSI BERAS LOKAL SIAM SERINDIT DI KABUPATEN TAPIN - Fitri Mahyudi; Husinsyah; Yarna Hasiani (Chlorophyl, 2026)
Lawahan Village is located within the administrative area of Tapin Selatan District, Tapin Regency. This village is known as a producer of Siam Serindit Rice, a new diversified product. This research was conducted from April to June 2026 in Lawahan Village, South Tapin District, Tapin Regency, intentionally. Lawahan Village was chosen as the research location due to its local potential for processing Siamese Serindit rice. In this study, the types of data used were primary and secondary data. Primary data was collected using interviews and questionnaires, while secondary data was obtained from journals. The level of consumer satisfaction with Siam Serindit rice using the Customer Satisfaction Index (CSI) method obtained a value of 0.83, which is very satisfied because it is in the score range of 0.81 to 1.00. The attributes of Siam Serindit rice products that are considered important by consumers are packaging with a score of 4.61, labels with a score of 4.44, and prices with a score of 4.17. Management needs to improve its level of satisfaction with color attributes, and aroma is a key aspect of its importance. Consumers find the label and packaging attributes of Ansalog rice highly satisfactory and important, so management needs to maintain these attributes and include the business permit number on the label